An Essay on the Origin of the South Indian Temple - Ramanayya, N. Venkata, (Brill | Manohar Publishers & Distributors, 2024)
Dravidian art is one of the visible features which defines the South Indian form of architecture. Initially, Gramadevata was the South Indian village deity that was revered, as temples were not prevalent during the ancient times, particularly during the pre-Sangam and Sangam periods. Similarly, gravesites and stone rings were also seen as sites of worship. However, in the later period, the proto-Dravidian architectural style was developed under the Todas. With the emergence of dynasties in the early medieval period, such as Cholas, Pallavas, Cheras, Pandyas, and other ancient South Indian kingdoms, temple architecture began to develop rapidly. The author marks some of the prime features of the South Indian temple architecture, such as the origins and different forms of vimana. This book also covers the intersection between Buddhism and Hinduism, and how Buddhist architecture gave rise to the South Indian temple architecture.